The Effect Of Family Background, Lifestyle, And Association On Interest In The Entrepreneurship Of The Young Generation (Gen-Z) In Medan City - Nabila Arsi; Feby Aulia Safrin (Journal of Economics and Business (JECOMBI), 2023)
This study aims to determine the effect of family background, lifestyle, and association on interest in entrepreneurship in the younger generation in Medan City. Then it will be analyzed partially and simultaneously. This study uses a quantitative method with an associative approach. The sampling technique is Nonprobability Sampling and involves 100 respondents. Primary data is obtained directly by distributing questionnaires through a google form, while secondary data is obtained through a literature study. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the family background variable (X1) does not influence the interest in entrepreneurship, and the lifestyle variable (X2) and association (X3) significantly influence the interest in entrepreneurship. However, family background (X1), lifestyle (X2), and association (X3) together (simultaneously) affect the interest in entrepreneurship (Y). The coefficient of determination test shows that there is a fairly close relationship between family background, lifestyle, and association with an interest in entrepreneurship with an R-value of 0.904. Through the Adjusted R-value, it is also known that the variables of family background, lifestyle, and association with an interest in entrepreneurship contribute 81.2% while the remaining 18.8% is influenced by other variables not examined in this study.